Progress in multiaxial coupling mechanisms of osteoporosis: insights from systems medicine on immune-inflammatory interactions, hormonal regulation, and metabolic imbalance - Yan, Manli; Yang, Miyang; Cai, Yaoqian; Zhang, Baoqing; Lin, Dingkun; Li, Xiang (Frontiers in Endocrinology, 2026)
Osteoporosis (OP) is increasingly recognized as a systemic disorder involving crosstalk among immune-inflammatory, endocrine, and metabolic axes, rather than a condition driven solely by bone-mineral imbalance. This review synthesizes recent advances in understanding these axes and their coupling mechanisms. The immune-inflammatory axis, centered on Th17/Treg imbalance and cytokines such as IL-17 and IL-35, regulates osteoclastogenesis and osteogenesis while linking autoimmune diseases to bone loss. The endocrine axis, encompassing sex hormones, thyroid/adrenal/parathyroid hormones, and receptors such as LGR4, modulates bone remodeling through complex signaling networks and circadian rhythms. The metabolic axis, particularly glucose-lipid-uric acid homeostasis, influences bone fragility via energy metabolism, oxidative stress, and gut microbiota interactions. We propose that OP is best understood as a network disorder manifesting in the skeleton, necessitating a shift from single-target to multi-axis systems medicine approaches. However, much of the mechanistic evidence derives from preclinical models and observational studies; prospective clinical validation remains essential. Future research should prioritize elucidating inter-axis communication in human cohorts and developing integrated, biomarker-stratified therapeutic strategies to advance precision management of osteoporosis.